Exploring the Therapeutic Potential of Herbal Plants in Managing Blood Sugar Levels: A Comprehensive Evaluation - Archita Katrolia; Ved Pal; Vikesh Kumar Shukla; Rohit Singh (Pharmacognosy Research, 2023)
Hyperglycemia, characterized by persistently high blood glucose levels due to insufficient insulin release or insulin resistance, is a major global health concern. The World Health Organization (WHO) reports a substantial increase in the number of diabetic patients, from 108 million in 1980 to 422 million in 2014, and further to 463 million in 2020. As a result, there has been a growing demand for medicinal plants to address this issue. Traditional medicine has long recognized and utilized various medicinal herbs with hypoglycemic properties. This review focuses on eight specific medicinal plants: Ficus religiosa (Moraceae), Syzygium cumini (Myrtaceae), Momordica charantia (Cucurbitaceae), Curcuma longa (Zingiberaceae), Ocimum tenuiflorum (Lamiaceae), Morinda citrifolia (Rubiaceae), Trigonella foenum-graecum Linn. (Fabaceae), and Peganum harmala (Zygophyllaceae), which have been found to play a significant role in managing hyperglycemia. The article explores the phytochemical constituents of these plants responsible for their hypoglycemic effects and elucidates their mechanisms of action. By providing a comprehensive review of these medicinal plants, this article offers valuable insights into their potential use for managing hyperglycemia.
Keywords: Herbal plants; Hyperglycemia; Insulin resistance; Phytoconstituents; Therapeutic potential.